Comparison of Bivalirudin Versus Heparin(s) During Percutaneous Coronary Interventions in Patients Receiving Prasugrel: A Propensity‐Matched Study. Issue 1 (1st October 2013) - Hamon, Martial; Bonello, Laurent; Marso, Steven; Rao, Sunil V.; Valgimigli, Marco; Verheugt, Freek; Gershlick, Anthony; Wang, Yamei; Prats, Jayne; Steg, Gabriel P.; Deliargyris, Efthymios
Abstract Background Several percutaneous coronary intervention (PCI) trials have established that the use of bivalirudin (BIV) is associated with improved patient outcomes and substantial hospital cost savings, relative to heparin (HEP)‐based regimens ± glycoprotein IIb/IIIa inhibitors (GPIs). Whether these benefits persist with the use of prasugrel, a new third‐generation oral thienopyridine, has not been previously evaluated. Methods Using the Premier hospital database, 6986 patients treated with prasugrel who underwent elective, urgent, or primary PCI between quarter 3, 2009 and quarter 4, 2010 from 166 US hospitals were identified. These patients received either BIV (n = 3377) or HEP ± GPI (n = 3609) as procedural anticoagulation. Outcomes of interest included bleeding, transfusions, death, and hospital length of stay (LOS). To control for patient and hospital‐level characteristics, propensity score‐matching (PSM) analyses were performed. Results Mortality, clinically apparent bleeding, clinically apparent bleeding requiring transfusion, any transfusions, and LOS were all lower in patients treated with BIV as compared with patients treated with HEP ± GPI. After PSM, the rate of transfusion was significantly lower with BIV (odds ratio: 0.57, 95% confidence interval: 0.34‐0.96), and the hospital LOS was significantly shorter in patients treated with BIV compared with those treated with HEP ± GPI (0.9 ± 2.0 vs 1.2 ± 2.3 days, P < 0.0001). Conclusions In patients undergoing PCI and treated with prasugrel, the use of BIV rather than HEP ± GPI is associated with significantly lower transfusion rate and LOS. These results suggest that the previously documented safety and cost‐effectiveness benefits of BIV remain applicable when prasugrel is used.